2020
DOI: 10.1186/s40798-020-0238-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Concentration Changes in Humans After a Bout of Exercise: a Systematic Review of Exercise Metabolomics Studies

Abstract: Background: Exercise changes the concentrations of many metabolites, which are small molecules (< 1.5 kDa) metabolized by the reactions of human metabolism. In recent years, especially mass spectrometry-based metabolomics methods have allowed researchers to measure up to hundreds of metabolites in a single sample in a non-biased fashion. To summarize human exercise metabolomics studies to date, we conducted a systematic review that reports the results of experiments that found metabolite concentrations changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
150
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(176 citation statements)
references
References 75 publications
24
150
1
1
Order By: Relevance
“…Interestingly, the TCA metabolites citric acid, malic acid and alpha ketoglutaric acid (aKG) were all higher in plasma after exertion ( Figure 2—figure supplement 1C ), suggesting release of these metabolites from muscle into plasma ( Figure 2—figure supplement 1D ). Contribution of muscle citrate to plasma has previously been shown; for example, by femoral arterio-venous sampling during exercise in human subjects ( Nielsen and Thomsen, 1979 ; Schranner et al, 2020 ).…”
Section: Resultsmentioning
confidence: 90%
“…Interestingly, the TCA metabolites citric acid, malic acid and alpha ketoglutaric acid (aKG) were all higher in plasma after exertion ( Figure 2—figure supplement 1C ), suggesting release of these metabolites from muscle into plasma ( Figure 2—figure supplement 1D ). Contribution of muscle citrate to plasma has previously been shown; for example, by femoral arterio-venous sampling during exercise in human subjects ( Nielsen and Thomsen, 1979 ; Schranner et al, 2020 ).…”
Section: Resultsmentioning
confidence: 90%
“…Lifestyle is known to be able to influence bile acid levels, for example directly after exercise, bile acid concentrations are reduced as compared to before exercise. Conversely, adherence to a Mediterranean diet has elevated the amounts of faecal bile acids [110,111]. In obese persons, a higher intake of fibre and protein also increased the levels of bile acids in serum [112].…”
Section: Atherosclerosis and Metabolites: Bile Acidsmentioning
confidence: 99%
“… Contrepois et al (2020) recently performed longitudinal profiling of blood metabolites before and after acute exercise in human and found 728 metabolites affected by exercise. Schranner et al (2020) identified 196 metabolites that are significantly changed by endurance or resistance exercise in human. These data might be a useful resource to investigate mechanisms of exercise-induced health benefits.…”
Section: Discussionmentioning
confidence: 99%
“…These factors contribute to the beneficial effects of exercise, including reduction of adipose mass and inflammation, maintenance of muscle mass, improvement of cardiovascular fitness, and promotion of brain plasticity, as discussed in many previous studies ( Hawley et al, 2014 ). Various types of exercise change whole-body metabolism in both clinical and animal models ( Huffman et al, 2014 ; Starnes et al, 2017 ; Sato et al, 2019 ; Schranner et al, 2020 ). Metabolism plays a crucial role in human health and disease, and is modulated by intrinsic and extrinsic factors.…”
Section: Introductionmentioning
confidence: 99%